The Role of Decentralized Health Systems in Shaping Service Quality: A Systematic Review in Low- and Middle-Income Countries - Eri Witcahyo Witcahyo; Asobat Gani; I Made Suwandi (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Decentralization has emerged as a prominent strategy for health sector reform in low- and middle-income countries (LMICs), aiming to enhance service quality, efficiency, equity, and responsiveness. This study systematically reviews literature published between 2021 and 2025 to explore the role of decentralized health systems in shaping healthcare service quality across LMICs. Using PRISMA 2020 guidelines, 20 eligible studies were identified and analyzed from databases including PubMed, Scopus, Web of Science, and Google Scholar. Thematic synthesis of findings reveals mixed outcomes: while decentralization improves local responsiveness, enhances community engagement, and strengthens health system performance in some settings, it also exacerbates disparities in others due to uneven institutional capacity, limited fiscal resources, and fragmented coordination. Key performance areas identified include human resource deployment, financing, access to services, and equity in service delivery. The study emphasizes the significance of local capacity-building, efficient resource allocation, and integrated planning in attaining sustainable and equitable healthcare improvements within decentralized systems. This review provides practical insights for policymakers aiming to align decentralization strategies with health equity and service quality objectives.